Regional sea-level highstand triggered Holocene ice sheet thinning across coastal Dronning Maud Land, East Antarctica - Suganuma, Yusuke; Kaneda, Heitaro; Mas e Braga, Martim; Ishiwa, Takeshige; Koyama, Takushi; Newall, Jennifer C.; Okuno, Jun’ichi; Obase, Takashi; Saito, Fuyuki; Rogozhina, Irina; Andersen, Jane Lund; Kawamata, Moto; et al. (Communications Earth & Environment, 2022)
The East Antarctic Ice Sheet stores a vast amount of freshwater, which makes it the single largest potential contributor to future sea-level rise. However, the lack of well-constrained geological records of past ice sheet changes impedes model validation, hampers mass balance estimates, and inhibits examination of ice loss mechanisms. Here we identify rapid ice-sheet thinning in coastal Dronning Maud Land from Early to Middle Holocene (9000–5000 years ago) using a deglacial chronology based on in situ cosmogenic nuclide surface exposure dates from central Dronning Maud Land, in concert with numerical simulations of regional and continental ice-sheet evolution. Regional sea-level changes reproduced from our refined ice-load history show a highstand at 9000–8000 years ago. We propose that sea-level rise and a concomitant influx of warmer Circumpolar Deep Water triggered ice shelf breakup via the marine ice sheet instability mechanism, which led to rapid thinning of upstream coastal ice sheet sectors.
Keywords: Antarktis; Sørishavet; glasiologi; havis; havnivå; isshelf

Basal Melt and Freezing Rates From First Noble Gas Samples Beneath an Ice Shelf - Huhn, Oliver; Hattermann, Tore; Davis, Peter E D; Dunker, Erich; Hellmer, Hartmut H; Nicholls, Keith W; Østerhus, Svein; Rhein, Monika; Schröder, Michael; Sültenfuß, Jürgen (Geophysical Research Letters, 2018)
A climatically induced acceleration in ocean-driven melting of Antarctic ice shelves would have consequences for both the discharge of continental ice into the ocean and thus global sea level, and for the formation of Antarctic Bottom Water and the oceanic meridional overturning circulation. Using a novel gas-tight in situ water sampler, noble gas samples have been collected from six locations beneath the Filchner Ice Shelf, the first such samples from beneath an Antarctic ice shelf. Helium and neon are uniquely suited as tracers of glacial meltwater in the ocean. Basal meltwater fractions range from 3.6% near the ice shelf base to 0.5% near the sea floor, with distinct regional differences. We estimate an average basal melt rate for the Filchner-Ronne Ice Shelf of 177 ± 95 Gt/year, independently confirming previous results. We calculate that up to 2.7% of the meltwater has been refrozen, and we identify a local source of crustal helium.
Keywords: Sørishavet; Weddellhavet; bunnvann; glasiologi; havnivå; innlandsis; isbrem; klimatologi; oseanografi; smelting; vannmasser

Channelized Melting Drives Thinning Under a Rapidly Melting Antarctic Ice Shelf - Gourmelen, Noel; Goldberg, Dan N; Snow, Kate; Henley, Sian F; Bingham, Robert G; Kimura, Satoshi; Hogg, Anna E; Shepherd, Andrew; Mouginot, Jeremie; Lenaerts, Jan T M; Ligtenberg, Stefan R M; van de Berg, Willem Jan (Geophysical Research Letters, 2017)
Ice shelves play a vital role in regulating loss of grounded ice and in supplying freshwater to coastal seas. However, melt variability within ice shelves is poorly constrained and may be instrumental in driving ice shelf imbalance and collapse. High-resolution altimetry measurements from 2010 to 2016 show that Dotson Ice Shelf (DIS), West Antarctica, thins in response to basal melting focused along a single 5 km-wide and 60 km-long channel extending from the ice shelf's grounding zone to its calving front. If focused thinning continues at present rates, the channel will melt through, and the ice shelf collapse, within 40–50 years, almost two centuries before collapse is projected from the average thinning rate. Our findings provide evidence of basal melt-driven sub-ice shelf channel formation and its potential for accelerating the weakening of ice shelves.
Keywords: Sørishavet; glasiologi; havnivå; innlandsis; isbrem; isshelf; smelting

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi